Bioinorganic chemistry of trace elements: Possible role in the epigenetic modulation of homoeostatic processes in complex organisms - Ratti, Silvia Gabriela (2013)
Trace elements are well known in the geochemistry disciplines. However, its relationship to the biological and medical sciences is very recent. In spite that knowledge about the influence of environment in living processes is a traditional concept, until about the middle part of the 20 century, the possible influence on physiological functions of chemical elements present in waters and soil surrounding man habitat was not particularly investigated. Principal concern was concentrated to evaluate toxic actions of chemical elements on living systems. However, evidence showing that chemical elements are able to interact with enzymes, transcription factors and DNA in several living systems, put the inorganic elements into a new perspective. Higher concentrations of inorganic elements in the environment do not necessarily must be the only requirement for biological interactions in living systems. In the present paper historical aspects, some chemical properties of trace elements, an emphasized discussion about selenium and tellurium on functional processes in living systems are reviewed. In addition, hypothesis about the role of trace elements on epigenetic changes in the expression of gene action is also discussed.